Using earnings and residual income in the valuation of newly listed firms - Νεγκάκης Χρήστος Ι. (SPOUDAI Journal of Economics and Business, 2006)
The present paper uses a set of valuation models which are based on Feltham and Ohlson's (1995) model, and examines the relationship between Market values (MV), Book values (BV) Net Income (NI), Residual Income (RI), and Research and Development (RD) expenses over a sample of newly listed US firms for the period 2000-2004. The purpose is to assess the extent to which traditional valuation methods remain valid in the new economic settings after the collapse of international markets in March 2000. Moreover, it is tested if the replacement of RI with NI in valuation models for newly listed firms potentially reduces information content and significance. The results indicate that variants of the Feltham and Ohlson's (1995) model, are able to explain the variation in MV of newly listed firms. Additionally, RI displays no stronger association than NI with MV of newly listed firms. Last, the results indicate that RD expenditures and BV enhance the explanatory power of both NI and RI for MV and their inclusion in valuation models is supported by the present study. JEL Classifications: G30, M40